IMPLEMENTASI PELIBATAN MASYARAKAT (ORANG TUA) DALAM KEGIATAN SEKOLAH DI SD ISLAM TERPADU AL-FATIH MAKASSAR - Nur Lisyah Fitaloka Syahrir; Wahira, Wahira; Sumarlin Mus (Nusantara Hasana Journal, 2025)
Parental involvement in school activities is a strategic element in building synergy between schools and families to support holistic child growth and development, especially in an integrated Islamic school environment that integrates academic and spiritual values. This study aims to describe and analyze the implementation of community involvement, especially parental involvement, in school activities at Al-Fatih Integrated Islamic Elementary School, Makassar. Using a descriptive qualitative approach, data were obtained through in-depth interviews, participant observation, and documentation, which were analyzed thematically with the help of software. The results of the study identified two main forms of parental involvement: internal activities, such as Parent Meetings, report card receptions, and the Ramadan Festival, which demonstrate direct and intensive interaction between the school and parents; and external activities, such as Al-Fatih Quran Family and Matapena, which demonstrate the school's efforts to expand the role of parents in supporting character formation and strengthening religious values outside the school environment. These findings indicate that parental involvement at Al-Fatih Integrated Islamic Elementary School, Makassar, is not only administrative, but also substantive and structured, in line with the principles of integrated Islamic education. This research provides theoretical and practical contributions in enriching the discourse on school and parent partnerships, and offers a model of parent involvement that can be adopted by other integrated Islamic schools to improve the quality of education comprehensively.